2019
DOI: 10.1080/14786419.2019.1630120
|View full text |Cite
|
Sign up to set email alerts
|

A new cytotoxic plumbagin derivative from roots of Diospyros undulata

Abstract: A new plumbagin derivative, 3-(5-oxohexyl)plumbagin (1), together with six known benzoquinone derivatives (2-7), four known triterpenoids (8-11) and coniferyl aldehyde (12) were isolated from Diospyros undulata roots. Their structures were elucidated by intensive spectroscopy including 1D and 2D NMR, UV, IR and MS spectrometric analysis. Compound 1 exhibited strong cytotoxicity against three cancer cell lines as lung cancer (NCI-H187), breast cancer (MCF-7), and oral cancer (KB) with IC 50 values of 7.16, 12.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Plumbagin has a variety of biological properties, including antioxidant, antiviral, antibacterial, antimalarial, and antiinflammatory activities (24,34). Some studies have shown that plumbagin has cytoxocity against various cancer cell lines including breast cancer, lung cancer, cervical cancer, leukemia, hepatocellular carcinoma, and oral cancer (34,35), but its adverse effects were extremely low (19,24,(36)(37)(38). For this reason, it has attracted increased attention and interest from researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Plumbagin has a variety of biological properties, including antioxidant, antiviral, antibacterial, antimalarial, and antiinflammatory activities (24,34). Some studies have shown that plumbagin has cytoxocity against various cancer cell lines including breast cancer, lung cancer, cervical cancer, leukemia, hepatocellular carcinoma, and oral cancer (34,35), but its adverse effects were extremely low (19,24,(36)(37)(38). For this reason, it has attracted increased attention and interest from researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can meet the advantages of multi-target therapy. [27] In addition to anticancer activity, plumbagin also has antimicrobial activity, which will be described in detail in the following section.…”
Section: Natural 14-nq Analogsmentioning
confidence: 99%
“…It can produce anticancer activity through apoptosis, autophagy, cell cycle arrest, antiangiogenesis, anti‐invasion, antimetastasis pathway, and other mechanisms. Therefore, it can meet the advantages of multi‐target therapy [27] . In addition to anticancer activity, plumbagin also has antimicrobial activity, which will be described in detail in the following section.…”
Section: Introductionmentioning
confidence: 99%